Pengaruh Teknik Self-Management terhadap Kecanduan Game Online Siswa di Madrasah Aliyah Yppt Lede - Nento, Asnarita; Dunggio, Arifah Abd. Latif; Bombae, Robin (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This research aims to find out whether self-management techniques influence online game addiction among Madrasah Aliyah YPPT LEDE students by using questionnaire data collection techniques and recording methods. Based on the results of the research conducted, it can be seen that there is a positive and significant influence between self-management techniques on online game addiction of Madrasah Aliyah YPPT LEDE students, this is shown from the results of simple linear regression calculations. , specifically Y = 23.551 + 0.520 This means that if self-management techniques increase by one value, the value of online game addiction will increase by 0.520. The tcount value obtained is 2.28, this value is higher than the ttable value of 1.782, meaning that there is a significant influence between the self-management technique variable and the online game addiction variable for Madrasah Aliyah YPPT LEDE students